Attitudes of pediatricians toward Children's consumption of ionic beverages - Akihisa Okumura; Shinobu Ida; Masaaki Mori; Toshiaki Shimizu; On behalf of the Committee on Pediatric Nutrition of The Japanese Pediatric Society (BMC, 2018)
Abstract Background The aim of our study was to clarify the attitudes of pediatricians toward children's consumption of ionic beverages. Methods A questionnaire survey of pediatric practitioners' attitudes toward the consumption of ionic beverages was administered to 537 doctors under 60 years of age who were members of the Japanese Pediatric Society. Results We received 215 valid responses from 182 board-certified pediatric specialists and 31 non-specialists. Approximately 60% of respondents recommended ionic beverages either often or sometimes. About half of all respondents cautioned patients about excessive consumption. About 40% had experienced at least one instance of excessive consumption characterized by acute symptoms including vomiting, diarrhea, and pyrexia. Specialists were more likely to recommend ionic beverages for oral rehydration than did non-specialists. Non-specialists more often recommended ionic beverages to patients with pyrexia. Conclusions Pediatricians' attitudes toward children's consumption of ionic beverages were generally appropriate. Pediatric specialists' attitudes were more appropriate than were those of non-specialists.